2021
DOI: 10.1007/s12519-021-00451-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of coxsackievirus A16 circulating in children in Beijing, China from 2010 to 2019

Abstract: Background Coxsackievirus A16 (CVA16) is one of the major etiological agents of hand, foot and mouth disease (HFMD). This study aimed to investigate the molecular epidemiology and evolutionary characteristics of CVA16. Methods Throat swabs were collected from children with HFMD and suspected HFMD during 2010–2019. Enteroviruses (EVs) were detected and typed by real-time reverse transcription-polymerase chain reaction (RT-PCR) and RT-PCR. The genotype, evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…36 in 2013 and during 2015-2019 in Beijing. 11 The etiological and phylogenetic analysis of HFMD in southern China showed that the predominant virus was also CV-A6 in 2020. 37 The analysis of symptoms caused by different pathogens suggested that the rash in patients affected by CV-A6 and Other enteroviruses spread to a wider distribution, and CV-A6 even on the face.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…36 in 2013 and during 2015-2019 in Beijing. 11 The etiological and phylogenetic analysis of HFMD in southern China showed that the predominant virus was also CV-A6 in 2020. 37 The analysis of symptoms caused by different pathogens suggested that the rash in patients affected by CV-A6 and Other enteroviruses spread to a wider distribution, and CV-A6 even on the face.…”
Section: Discussionmentioning
confidence: 99%
“…10 The prevalence of CV-A16 showed obvious periodic fluctuations in Beijing from 2010 to 2018, with the detection rate increasing every other year. 11 Nonetheless, in recent years, CV-A6-associated HFMD outbreaks 12,13 and the overall trend of the epidemic of CV-A6-associated HFMD was increasing in China. 14 The clinical features of CV-A6-associated HFMD are slightly different from representing so-called atypical HFMD, with the skin eruptions spreading to the trunk, neck, and legs, and high fever with a shorter duration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to EV71, CVA16 was considered the predominant agent responsible for the HFMD outbreaks in many regions of China in the last decade [2,[19][20][21]. Phylogenetically, there are three genotypes of CV-A16 (Genotypes A, B and D) detected worldwide [19].…”
Section: Discussionmentioning
confidence: 99%
“…CV-A6 was detected a high proportion in HFMD or herpangina children in vast locations and time span ( 16 ), and it was the predominant pathogen in Guangdong in 2015, Singapore in 2013-2018 and Guizhou in 2019 ( 17 , 18 ). Studies ( 19 ) showed that CV-A6 detection rate was low in 2010-2012, then increased in 2013, 2015, 2017 and remained high in 2018, while decreased in 2014, 2016 and 2019. Combined with that study, our result of CV-A6 detection rate increasing from 2019 to 2020 reflected that CV-A6 strains rose epidemic peak every 2 years.…”
Section: Discussionmentioning
confidence: 99%